Molecular Biology and Biotechnology of Plant Organelles Chloroplasts and Mitochondria - Daniell, Henry; Chase, Christine (Springer Netherlands, 2004)
We have taught plant molecular biology and biotechnology at the undergraduate and graduate level for over 20 years. In the past few decades, the field of plant organelle molecular biology and biotechnology has made immense strides. From the green revolution to golden rice, plant organelles have revolutionized agriculture. Given the exponential growth in research, the problem of finding appropriate textbooks for courses in plant biotechnology and molecular biology has become a major challenge. After years of handing out photocopies of various journal articles and reviews scattered through out the print and electronic media, a serendipitous meeting occurred at the 2002 IATPC World Congress held in Orlando, Florida. After my talk and evaluating several posters presented by investigators from my laboratory, Dr. Jacco Flipsen, Publishing Manager of Kluwer Publishers asked me whether I would consider editing a book on Plant Organelles. I accepted this challenge, after months of deliberations, primarily because I was unsuccessful in finding a text book in this area for many years. I signed the contract with Kluwer in March 2003 with a promise to deliver a camera-ready textbook on July 1, 2004. Given the short deadline and the complexity of the task, I quickly realized this task would need a co-editor. Dr. Christine Chase was the first scientist who came to my mind because of her expertise in plant mitochondria, and she readily agreed to work with me on this book
Keywords: Plant Sciences; Cell Biology; Plant Biochemistry; Plant Physiology; Plant Genetics and Genomics; Botany; Cytology; Biochemistry; Plant physiology; Plant genetics; Chloroplast; Pflanzenzelle; Biotechnologie; Molekularbiologie; Mitochondrium; Aufsatzsammlung